SEGREGATION AND AUTHORITY IN LATE-MEDIEVAL INDIA: WOMEN, THE HAREM, AND THE HUMAYUN-NAMA PERSPECTIVE - Abu Hurara; Raheem Ullah; Hassan Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
This article provide a glimpse into the complexities of gender dynamics within the Mughal Empire, focusing on the late-medieval period as portrayed in the Humayun-Nama. This paper examines how the Humayun-Nama illustrates the impact of the Mughal harem on the segregation and authority of women, exploring how this depiction both challenged and reinforced the gender dichotomy prevalent in late-medieval India. The study highlights the enduring patterns of segregation and authority, revealing that the Mughal society largely perpetuated earlier patriarchal structures. Relying on Gulbadan’s account, it reveals that how women’s roles, including aspects of beauty, love, and motherhood, were reflected and influenced by their societal status and equality within the Mughal harem practices. Similarly, the paper explores why the Mughal Empire implemented specific institutional practices regarding the harem, as described in the Humayun-Nama, and how these practices contributed to the construction of gender dynamics and the authoritative representation of women in Mughal society. This inquiry assumed the complexities of women’s experiences and the multifaceted nature of their roles within a male-dominated framework of segregation and authority.